Intrafamilial variability in the clinical manifestations of mucopolysaccharidosis type II: Data from the Hunter Outcome Survey (HOS). Issue 2 (6th December 2017) - Ficicioglu, Can; Giugliani, Roberto; Harmatz, Paul; Mendelsohn, Nancy J.; Jego, Virginie; Parini, Rossella
Abstract : Several cases of phenotypic variability among family members with mucopolysaccharidosis type II (MPS II) have been reported, but the data are limited. Data from patients enrolled in the Hunter Outcome Survey (HOS) were used to investigate intrafamilial variability in male siblings with MPS II. As of July 2015, data were available for 78 patients aged ≥5 years at last visit who had at least one affected sibling (39 sibling pairs). These patients were followed prospectively (i.e., they were alive at enrollment in HOS). The median age at the onset of signs and symptoms was the same for the elder and younger brothers (2.0 years); however, the younger brothers were typically diagnosed at a younger age than the elder brothers (median age, 2.5 and 5.1 years, respectively). Of the 39 pairs, eight pairs were classified as being discordant (the status of four or more signs and symptoms differed between the siblings); 21 pairs had one, two, or three signs and symptoms that differed between the siblings, and 10 pairs had none. Regression status of the majority of the developmental milestones studied was generally concordant among siblings. Functional classification, a measure of central nervous system involvement, was the same in 24/28 pairs, although four pairs were considered discordant as functional classification differed between the siblings. Overall, this analysis revealed similarity in the clinical manifestations of MPS II among siblings. This information should help to improve our understanding of the clinical presentation of the disease, including phenotype prediction in affected family members.